Strategies for Solving a Problem of People’s Poverty Based on King’s Science - Suwan, Manat; Foosang, Saman; Choonrum, Narongphan; Wattanaluangarun, Worapol; Suwan, Chontanat (Ganesha Journal, 2021)
Among various factors as obstacles for the country development, people’s poverty may be considered to be the most significant one. Income poverty is a major barrier for economic stimulation due to the lack of purchasing power. Meanwhile, human poverty can cause the production processes because of the shortage of working knowledge and skills, as well as health problems due to the lack of accessing to public welfare. Every government in the past has tried to put efforts to find and implement various measures to solve such problems of people’s poverty. But it seemed like the situations have been even worst, because the rich keep getting richer and the poor keep getting poorer. This article is presented the analysis of poverty context in Thailand. It begins with reviewing of the poverty situations and causal factors, then follows by the analysis of success and/or failure of the problem solution and its causal factors. The analysis results can be collectively concluded that the governments’ efforts to solve problems of the people’s poverty are not succeeded as there should be as follows: (1) there is not thoroughly understand what are the real causes of the poverty, (2) the problem solution measures are inappropriate with the context of the Thai society, (3) a lack of people’s participation, and (4) too much rigorously adherence with theories rather than practicality. It is the suggestion from this study that there is possible success to solve the people’s poverty, the problem solution measures must be improved to be the most accuracy, suitability, and possibility. There are 8 strategies recommended based on King Rama IX Work Principles namely: (1) emphasizing on the Principle of “Systematic Study of Information”; (2) applying of “Local Wisdom” with “Modern Technology”; (3) balancing between “Topography” and “Sociology”; (4) using “Holistic Approach”; (5) emphasizing on “Human Poverty” rather than “Monetary Poverty”; (6) practicing of “Sufficiency Economy Principle”; (7) applying “People Participation” Principle; and (8) applying of “Appropriate Technology”.